Asymmetric Effect of Oil Price on Economic Activity: Evidence from Lebanon Using NARDL Model - Fakhreddine, Nour; Najia, Noura; Mourad, Abbas; Nasser, Wafaa (International Journal of Energy Economics and Policy, 2024)
The aim of this paper is to investigate the impact of oil prices on the real economic activity of Lebanon, represented by the Gross Domestic Product (GDP) while controlling for inflation. For this purpose, this study employs a non-linear auto-regressive distributed lag model (NARDL) that enables to take into consideration the asymmetrical nature of the relationship between these two variables. The empirical findings confirm the asymmetric impact of changes in oil prices on economic activity. Notably, reductions in oil prices positively influence GDP in the long term and exert a more pronounced fluctuating effect compared to increases in oil prices, which are statistically insignificant. In other words, the country’s GDP, serving as a measure of the total value of finished goods and services, does not respond significantly to oil price rises but is influenced by oil price reductions. This empirical analysis focuses particularly on Lebanon, and time series data spanning from 1988 to 2021 are used to explore this relationship. This study guides Lebanon's policymakers, revealing the impact of declining oil prices on economic activity. It highlights growth opportunities amidst challenges like economic crises and corruption. Advocating for prudent policies and strategies, it offers a pathway for sustainable development.